(untitled) (Docentes 2.0 Journal, 2024)
The relevance of research skills in higher education is undeniable, establishing themselves as pillars for the progress and achievement of academic initiatives and the attainment of academic degrees. This analysis focuses on the impact of work habits, individual qualities, and research skills, especially their connection with using information and communication technologies (ICT), in postgraduate students. Through a quantitative method and a positivist framework, using a non-experimental, cross-sectional, and correlational design, a survey was conducted on 25 students from two Peruvian higher education institutions, one public and the other private, using the questionnaire on competencies and contexts for the development of postgraduate research developed by Gonzáles et al. (2016). The results reveal a moderate to high positive correlation between scientific-intellectual and technical competencies, individual qualities and technical skills, and work habits and personal attributes in both institutions. The synergy between research skills’ cognitive, individual, and technical components is emphasized. The research shows that these competencies are multifaceted, involving highly complex cognitive processes and using specific tools and methodologies effectively. Additionally, it underscores the imperative to promote holistic development in students, harmonizing technical skills with personal qualities within the framework of ICT use. Such a holistic approach is fundamental to enhancing the investigative capacity of postgraduate learners, highlighting the need to cultivate a strong research culture that effectively incorporates ICT into the educational dynamic.